The weirdo - Taylor, Theodore, 1921-2006. (New York : Avon Book, 1993)
Seventeen-year-old Chip Clewt fights to save the black bears in the Powhaten National Wildlife Refuge.
Notable/Best Books (A.L.A.).
School Library Journal.
Wilson's Junior High School.
4.7
Young Adult
Keywords: Bears -- Fiction; Swamps -- Fiction; Wildlife conservation -- Fiction; Bears -- Fiction; Swamps -- Fiction; Wildlife conservation -- Fiction; North Carolina -- Fiction; North Carolina -- Fiction